Successfully Climbing the “STAIRs”: Surmounting Failed Translation of Experimental Ischemic Stroke Treatments - Michael P. Kahle; Gregory J. Bix (Stroke Research and Treatment)
The Stroke Therapy Academic Industry Roundtable (STAIR) provided initial (in 1999) and updated (in 2009) recommendations with the goal of improving preclinical stroke therapy assessment and to increase the translational potential of experimental stroke treatments. It is important for preclinical stroke researchers to frequently consider and revisit these concepts, especially since promising experimental stroke treatments continue to fail in human clinical trials. Therefore, this paper will focus on considerations for several key aspects of preclinical stroke studies including the selection and execution of the animal stroke model, drug/experimental treatment administration, and outcome measures to improve experimental validity and translation potential. Specific points of interest discussed include the incorporation of human comorbid conditions and drugs, the benefits of defining a proposed mechanism of action, replication of results using multiple methods, using clinically relevant routes of administration and treatment time windows, and performing and reporting good experimental methods to reduce bias such as, as suggested by the updated STAIR recommendations, sample size calculations, randomization, allocation concealment, blinding, and appropriate inclusion/exclusion criteria. It is our hope that reviewing and revisiting these considerations will benefit researchers in their investigations of stroke therapies and increase the likelihood of translational success in the battle against stroke.